Embracing the duality of consideration and initiating structure: CEO leadership behaviors and small firm performance. Issue 3 (20th April 2020) - Basker, Inger N.; Sverdrup, Therese E.; Schei, Vidar; Sandvik, Alexander M.
Abstract : Purpose: This paper examines the relationship between chief executive officers' (CEOs') leadership behaviors (consideration and initiating structure) and firm and individual performance (i.e. profitability, affective commitment and employees' willingness to change) in small and medium-sized firms (SMEs) that need to adapt to changing environments. Design/methodology/approach: Survey data was collected from SMEs (28 firms, 235 employees) in the accounting industry along with objective performance register data (profit and return on assets). The predicted model was tested with multilevel structural equations modeling (MSEM) using a maximum likelihood estimator. Findings: The CEO leadership behavior of initiating structure was positively related to firms' profitability, while the CEO leadership behavior of consideration was positively related to employees' willingness to change and affective commitment. Practical implications: Small accounting firms typically offer standard services that are now being replaced by digital solutions. These firms have an incentive to offer new services, such as business advisory services. Therefore, leaders should embrace the duality of consideration and initiating structure to gain employees' willingness to change and optimize overall firm performance. Originality/value: The paper contributes to leadership literature by examining a novel context (CEO consideration and initiation of structure in SMEs in uncertain environments) using a combination of firm performance measures (e.g. objective outcomes at the firm level and employees' willingness to change as a new measure at the individual level). In addition, it reports a comprehensive test of the full model using MSEM, the findings of which demonstrate the importance of dual leadership behaviors for CEOs.